Income, amenities and negative attitudes - Gisela Waisman; Birthe Larsen (IZA Journal of Migration, 2016)
We exploit the regional variation in negative attitudes towards immigrants to Sweden in order to analyse the consequences of negative attitudes on refugees' utility from labour income and amenities. We find that attitudes towards immigrants are important: while they affect mainly the refugees' quality of life, they also affect their income. We estimate the utility effects of negative attitudes for refugees with different levels of education and gender. We also analyse how the size of the refugees' networks relate to their quality of life and income as well as how negative attitudes towards immigration and networks interact.
Keywords: J15; J31; J61; J71; 330; Attitudes towards immigration; Geographical mobility; Income; Amenities